Two- and Three-Year-Olds Track a Single Meaning During Word Learning: Evidence for Propose-but-Verify. Issue 3 (2nd July 2016) - Woodard, Kristina; Gleitman, Lila R.; Trueswell, John C.
ABSTRACT: A child word-learning experiment is reported that examines 2- and 3-year-olds' ability to learn the meanings of novel words across multiple, referentially ambiguous, word occurrences. Children were told they were going on an animal safari in which they would learn the names of unfamiliar animals. Critical trial sequences began with hearing a novel word (e.g., "I see a dax! Point to the dax!") while seeing photos of two unfamiliar animals. After responding and performing on two filler trials with known animals, participants encountered the novel word again ("I see another dax! Point to the dax!") in one of two experimental conditions. In the Same condition, participants saw the animal they pointed to previously when hearing "dax" alongside another unfamiliar animal that had been seen before but not paired with "dax". In the Switch condition, participants saw the animal they had not pointed to previously alongside the unfamiliar animal. Children were well above chance on Same trials, but at chance on Switch trials. Thus, although children could remember a previously selected referent and use it to inform later referent selection (Same condition), a potential referent that was not previously selected and merely co-occurred with the target word (Switch condition) was either not remembered, or simply deemed irrelevant to word meaning. This finding suggests young children do not store multiple possible meanings from a single word occurrence, but rather restrict learning to what they deemed to be the unique referent of the novel word in the moment, testing that word-meaning hypothesis on the next occurrence.